2015
DOI: 10.1021/acs.macromol.5b01362
|View full text |Cite
|
Sign up to set email alerts
|

Lamellar Diblock Copolymers on Rough Substrates: Self-Consistent Field Theory Studies

Abstract: We present numerical calculations of lamellar phases of diblock copolymers (BCP) confined between two surfaces, where the top surface is flat and the bottom one is corrugated. The corrugated substrate is assumed to have a single q-mode of lateral undulations with a wavenumber q s and amplitude R. We focus on the effects of substrate roughness, parametrized by the dimensionless quantity, q s R, on the relative stability between parallel and perpendicular orientations of the lamellar phase. The competition betwe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 38 publications
6
24
0
Order By: Relevance
“…On the theoretical side [33][34][35][36][37][38], previous works have been mainly devoted to study the transition between parallel to perpendicular lamellar phases in presence of a substrate. Most of these studies have been done in two dimensions and cannot address the important experimental issues related to inplane alignment, which intrinsically requires a 3D study.…”
Section: Introductionmentioning
confidence: 99%
“…On the theoretical side [33][34][35][36][37][38], previous works have been mainly devoted to study the transition between parallel to perpendicular lamellar phases in presence of a substrate. Most of these studies have been done in two dimensions and cannot address the important experimental issues related to inplane alignment, which intrinsically requires a 3D study.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4 shows the phase transition between perpendicular and parallel orientations (C ⊥ -to-C ), and between the two parallel orientations themselves (C 2 -to-C 1 ) in terms of the substrate roughness, 2πR/L s , and the substrate preference, u. In previous studies, 29 it has been shown that there are two ways to change the substrate roughness. First we fix the L s = 3L a 0 and then change the amplitude R from 0.1 to 0.3, as shown in Fig- ures 4a and 4b.…”
Section: A the Unidirectional Substrate Corrugation Along The A-direc...mentioning
confidence: 99%
“…This is consistent with the results shown in Figure 4, and also with previous studies. 21,29,30 B. The unidirectional substrate corrugation along the b-direction…”
Section: A the Unidirectional Substrate Corrugation Along The A-direc...mentioning
confidence: 99%
See 1 more Smart Citation
“…Taking advantage of the dielectric constant difference of each block, orientation control of the BCP self-assembly can also be achieved by applying an external electric field, although it is generally limited to BCP films with micrometre-scale thickness 17 18 . In addition, surface topology modulation 19 20 , solvent annealing 21 22 and other methods 23 24 have also been proposed to control BCP microdomain orientation. Besides the perpendicular orientation, controlled BCP self-assembly with lateral order and localized nanostructures 25 26 27 28 is also necessary in practical lithography processes to realize pattern registration and addressable device-oriented patterns with low defects 29 30 .…”
mentioning
confidence: 99%